A utilização de redes sociais online na busca por oportunidades de trabalho e no recrutamento de profissionais: uma análise da rede social LinkedIn - Maymone, Diego Simões Corrêa (2013)
In recent years the Internet has become one of the most used channels for communicating job opportunities or positions, identifying talents and searching for jobs, allowing changes in the form of action and interaction between those who offer and those looking for a job. Companies and recruiters can now rely on the benefits that the expressive reach of the Internet brought to publishing job opportunities, while the professionals looking for a job have increased resources and tools available to conduct research for job opportunities published by companies in their corporate websites, in online classified ads and in other webbased services, such as online social networks. With the popularity of online social networks, new trends have emerged in the processes for recruitment and job search, fostering the construction of relationships and communities intended to leverage the experience of recruiters and professionals looking for a job. And, in face of this reality, this research aims at analyzing and describing how online social networks support the processes of recruiting and searching for job opportunities. In this exploratory descriptive research, for which the instrument used for collecting data was the bibliographical research, LinkedIn was identified and highlighted among the online social networks that appear as a tool to support the processes assessed herein. LinkedIn is a professional social network, whose role, potential and importance for the recruitment industry has grown as millions of professionals and businesses around the world create their online profiles/resumes, turning this social network into a place where employers and job seekers meet each other. Based on the work of authors like Cappelli, Qualman, Safko, Hunt, Anand, Khun & Skuterud, Santaella, Krueger, and others who study topics such as online social networks, the Internet and/or recruiting and job searching processes, as well as through the analysis of research conducted by Comscore, Jobvite, Bullhorn, and LinkedIn, the present study provided information that proves the high potential of online social networks as being tools to support the processes of recruitment and job search, and identifies and presents the benefits that LinkedIn has brought to the recruiting and job searching processes in Brazil and worldwide